Gender Performance By Miranda Priestly As The Main Character In Weisberger’s The Devil Wears Prada - Murtazikoh, Baety; Hetami, Fatma (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2022)
This research was aimed to describe the gender performance of Miranda Priestly as the main character in Weisberger’s The Devil Wears Prada. As the data of the study were in the form of sentences, dialogue, phrases, and narrative, a qualitative method is served by using a literature review. It is chosen because the qualitative method is based on human behaviors or actions. Furthermore, this study also analyzed gender and feminism as a part of human behaviors and actions . In analyzing the data, the researcher used Judith Butler’s postmodernism feminist theory as an approach to describe gender performance in Weisberger’s The Devil Wears Prada. The result of the study indicates that Miranda Priestly’s gender performance is displayed through her general description and gender reconstruction. The findings show that through Miranda Priestly’s general description, her gender performance was described as an influential and successful chief editor of American Runway magazine. It further shows Miranda Priestly’s gender reconstruction by challenging the gender stereotypes toward women's characterizations and performing masculine traits. By reconstructing her gender, Miranda Priestly’s gender performance reveals that gender is performative and carries a variety of actions or behaviors that are revised, updated and transformed throughout time.